Radial growth response to climate change along the latitudinal range of the world's southernmost conifer in southern South America - Holz, Andres; Hart, Sarah J.; Williamson, Grant J.; Veblen, Thomas T.; Aravena Donaire, Juan Carlos (My University, 2018)
Aim: We examined whether and how tree radial-growth responses to climate have changed for the world's southernmost conifer species throughout its latitudinal distribution following rapid climate change in the second half of the 20th century. LocationTemperate forests in southern South America. Methods: New and existing tree-ring radial growth chronologies representing the entire latitudinal range of Pilgerodendron uviferum were grouped according to latitude and then examined for differences in growth trends and non-stationarity in growth responses to a drought severity index (scPDSI) over the 1900-1993 AD period and also before and after significant shifts in climate in the 1950s and 1970s. Results: The radial-growth response of P. uviferum climate was highly variable across its full latitudinal distribution. There was a long-term and positive association between radial growth and higher moisture at the northern and southern edges of the distribution of this species and the opposite relationship for the core of its distribution, especially following the climatic shifts of the 1950s and 1970s. In addition, non-stationarity in moisture-radial growth relationships was observed in all three latitudinal groups (southern and northern edges and core) for all seasons during the 20th century. Main conclusions: Climate shifts in southern South America in the 1950s and 1970s resulted in different responses in the mean radial growth of P. uviferum at the southern and northern edges and at the core of its range. Dendroclimatic analyses document that during the first half of the 20th century climate-growth relationships were relatively similar between the southern and northern range edges but diverged after the 1950s. Our findings imply that simulated projections of climate impacts on tree growth, and by implication on forest ecosystem productivity, derived from models of past climate-growth relationships need to carefully consider different and non-stationarity responses along the wide latitudinal distribution of this species.
Keywords: climate change; dendroclimatic variability; non-stationarity; patagonia; pilgerodendron uviferum